2009
DOI: 10.1016/j.ejvs.2009.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Distensibility of Forearm Veins in Haemodialysis Patients on Duplex Ultrasound Testing Using Three Provocation Methods

Abstract: Hydrostatic pressure combined with warmth generates the greatest venous distensibility in the lower arm in haemodialysis patients in a sitting position and is not significantly different compared to healthy volunteers. Without the superior provocation method, venous diameters of haemodialysis patients can be assessed as false-negatives yielding that a primary radio cephalic arteriovenous fistula (RCAVF) at wrist level (the first choice) in these patients will be withheld.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…To further complicate the situation, some authors have shown that there can be substantial overlap in the vein diameters of those whose AVF fail and those that succeed (7). Vein quality (e.g., distensibility) has not been studied extensively (59)(60)(61); however, the great majority of surgeons would not use a vein that appears sclerotic on either preoperative duplex ultrasound or direct examination. In such patients, re-evaluation is required to decide on an AV graft in the same location or an AVF with alternate vessels.…”
Section: Vein Size/qualitymentioning
confidence: 99%
“…To further complicate the situation, some authors have shown that there can be substantial overlap in the vein diameters of those whose AVF fail and those that succeed (7). Vein quality (e.g., distensibility) has not been studied extensively (59)(60)(61); however, the great majority of surgeons would not use a vein that appears sclerotic on either preoperative duplex ultrasound or direct examination. In such patients, re-evaluation is required to decide on an AV graft in the same location or an AVF with alternate vessels.…”
Section: Vein Size/qualitymentioning
confidence: 99%
“…The study of Korten et al showed that the change in vein size is comparable between healthy individual and dialysis patients towards various provocation methods [6]. Nonetheless, based on the result of the current study, a study with the same protocol should be performed on ESRD or renal impairment patients planned for vascular access surgery to confirm the response of their superficial vein towards environmental temperature.…”
Section: Discussionmentioning
confidence: 79%
“…The NKF-KDOQI guideline suggested that the preferable mean venous diameter should be ≥2.5 mm and arterial diameter ≥1.6 mm for successful AVF creation [8]. Different from artery, vein size may vary tremendously in response to body posture, stress, and external environment [5, 6]. One would therefore prefer that ultrasound vein size assessment captures the maximum potential of the vein to facilitate clinical decision and, hence, better outcome [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations